The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4081/aiua.2020.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of semirigid ureteroscopy, flexible ureteroscopy, and shock wave lithotripsy for initial treatment of 11-20 mm proximal ureteral stones

Abstract: Objective: We aimed to retrospectively evaluate the effectiveness and safety of flexible ureteroscopy (f-URS), semirigid ureteroscopy (sr-URS), and shock wave lithotripsy (SWL) to treat single 11-20 mm stones in the proximal ureter. Materials and methods: Patients treated at our clinic for 11-20 mm single stones in the proximal ureter who underwent f-URS, sr-URS or SWL as initial lithotripsy methods were compared in terms of their clinical characteristics and treatment outcomes. Results: A comparison among 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 21 publications
3
32
0
3
Order By: Relevance
“…In a study where they compared fURS with srURS in the treatment of upper ureteral stones, Kartal et al reported that operation times where fURS was performed were significantly longer. 4 Similar findings were also reported by Karadag et al 23 AlthoughÖzkaya et al reported that the use of UAS in patients who underwent fURS shortened the operation time compared to those who did not use UAS, Galal's study comparing fURS with URS showed that operation times where srURS was carried out were significantly shorter. 5,24 In our study, although the average length of operations using srURS were shorter than those using fURS, these differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In a study where they compared fURS with srURS in the treatment of upper ureteral stones, Kartal et al reported that operation times where fURS was performed were significantly longer. 4 Similar findings were also reported by Karadag et al 23 AlthoughÖzkaya et al reported that the use of UAS in patients who underwent fURS shortened the operation time compared to those who did not use UAS, Galal's study comparing fURS with URS showed that operation times where srURS was carried out were significantly shorter. 5,24 In our study, although the average length of operations using srURS were shorter than those using fURS, these differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 75%
“…Kartal et al reported that they could not find a significant difference in intraoperative complication rates between fURS and srURS in upper ureteral stones. 4 Karadag et al also reported that there was no difference in intraoperative complications. 23 Finally, Galal et al reported no significant difference between both intraoperative and postoperative complications.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Kartal et al compared treatment options for proximal ureteral stones and reported stone-free rates as 67.2% on the 15th postoperative day and 94.1% on the third postoperative month after semirigid URS. In the same study, stone-free rates for flexible URS were 89.6% and 97%, respectively [13]. Data in the literature demonstrate that urologists can achieve a high success rate for ureteral stones with semirigid URS.…”
Section: Discussionmentioning
confidence: 70%